Photogrammetry with Remotely Piloted Aircraf System for the Determination of Aerial Biomass in Urban Parks - Jennyfer F. Burgos Ochoa; Alexandra C. Melendez Jackson; Carlos A. Castaneda-Olivera; Danny A. Lzarzaburu Aguinaga (Chemical Engineering Transactions, 2022)
The exponential growth of the population is generating the deterioration of ecosystems due to its need to improve the quality of life, so the application of non-invasive methods for the management of natural resources such as trees in urban parks is sought. Therefore, in the present research, photogrammetry with Remotely Piloted Aircraf System (RPAs) was applied for the determination of aerial biomass in the parks of the district of Los Olivos in Lima, Peru. The study was conducted in five parks, which were previously georeferenced by a GPS to capture images with the Phantom 4 Pro drone. The images were processed with Agisoft software to calculate the aerial biomass and carbon sequestration of the trees. The results were given in tons of aerial biomass per hectare (t/ha) and tons of carbon sequestration per hectare (tC/ha); thus, Raimondi Park obtained 1,217 t/ha and 0. 572 tC/ha, Solidaridad Park obtained 1,848 t/ha and 0.868 tC/ha, Cristo Rey Park obtained 9,443 t/ha and 4,438 tC/ha, Juan Pablo II Park obtained 3,694 t/ha and 1,736 and Santa Rosa Park obtained 4,260 t/ha and 2,002 tC/ha. Based on the results, it is concluded that photogrammetry with RPAs is a favorable and efficient methodology that allows determining the aerial biomass and calculating carbon sequestration, helping to preserve green areas according to the number of inhabitants per urban area.